A Randomized, Placebo-controlled, Double-blind Pilot Study of Single-dose Humanized Anti-IL5 Antibody (Reslizumab) for the Reduction of Eosinophilia Following Diethylcarbamazine Treatment of Loa loa Infection. (10th September 2020) - Legrand, Fanny; Herrick, Jesica; Makiya, Michelle; Ramanathan, Roshan; Thompson, Reagan; Rampertaap, Shakuntala; Stoddard, Jennifer; Ware, JeanAnne; Fay, Michael P; Holland-Thomas, Nicole; Nutman, Thomas B; Klion, Amy D
Abstract: Background: Diethylcarbamazine citrate (DEC) treatment of loiasis is complicated by adverse reactions that are correlated with the number of circulating microfilariae (mf). The cause of these reactions is unknown, but they are accompanied by a dramatic interleukin-5 (IL-5)-dependent increase in eosinophilia and evidence of eosinophil activation. Methods: To explore the role of IL-5 driven eosinophilia in post-DEC reactions, 8 adults with confirmed loiasis and <5000 mf/mL blood were enrolled in a randomized, double-blind, placebo-controlled trial of the humanized anti-IL-5 antibody, reslizumab, (1.0 mg/kg IV) administered 3 to 7 days prior to initiation of DEC treatment (9 mg/kg/day for 21 days). The primary endpoint was the reduction in absolute eosinophil count (AEC) during the first week of DEC treatment. Results: Baseline characteristics were comparable between the two groups. Single dose reslizumab lowered the AEC by 77% prior to initiation of DEC therapy (vs. 12% in the placebo group, P < .05). More importantly, AEC remained below baseline in the first week of DEC treatment in all subjects who received reslizumab and in none of the placebo subjects. Mf clearance occurred within 2 days of initiation of DEC in all 7 mf-positive subjects. Mild to moderate adverse events were seen in all 8 subjects and were not significantly different between the groups. Conclusions: In summary, although reslizumab was able to blunt peripheral eosinophilia post-DEC treatment in subjects with loiasis and had no effect on microfilarial clearance, the reduction in AEC appeared to have been insufficient to prevent post-treatment AEs. Abstract : Post-treatment reactions in loiasis are accompanied by an IL-5 driven rise in eosinophil count. Pretreatment with reslizumab (anti-IL-5 antibody) blunted the eosinophil response postdiethylcarbamazine treatment without impeding microfilarial clearance but had no effect on post-treatment clinical manifestations.